Superman or the Fantastic Four? knowledge combination And experience in Innovative Teams - Taylor, Alva; Greve, Henrich R. (Academy of Management Journal, 2006)
This study focuses on effects of knowledge and experience on both mean and variance measures of individual and team innovations. We propose that multiple knowledge domains produce novel combinations that increase the variance of product performance and that extensive experience produces outputs with high average performance. We analyzed innovations in the comic book industry, finding that innovations with extreme success and failure were affected by factors similar to those affecting high-performing innovations. Multimember teams and teams with experience working together produced innovations with greater variation in value, but individuals were able to combine knowledge diversity more effectively than teams.